Explicație pas cu pas:
[tex]a) \: x + \frac{3}{5} = - 1 \frac{7}{10} \\ x + \frac{3}{5} = - \frac{17}{10} \\ x = - \frac{17}{10} - {}^{2)} \frac{3}{5} \\ x = - \frac{17}{10} - \frac{6}{10} \\ x = - \frac{23}{10} \\ \\ b) \: 4x - 5 = 6 \\ 4x = 6 + 5 \\ 4x = 11 \\ x = 11 \div 4 \\ x = 2.75 \\ \\ c) \: 2 \times (3x - 2) = - 3 \frac{5}{6} \\ 6x - 4 = - \frac{23}{6} \\ 6x = - \frac{23}{6} + {}^{6)} 4 \\ 6x = - \frac{23}{6} + \frac{24}{6} \\ 6x = \frac{1}{6} \\ x = \frac{1}{6} \div 6 \\ x = \frac{1}{6} \times \frac{1}{6} \\ x = \frac{1}{36} [/tex]
Succes!